2021
DOI: 10.1111/jocn.15679
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between patient obesity and nursing workload: An integrative review

Abstract: Aims and objectives:To explore the relationship between patient obesity and nursing workload, and discuss the nursing activities most affected by patient obesity. Background:The increasing number of patients with obesity, and the severity of obesity, impacts the healthcare workforce, particularly to nurses who provide most direct care to patients. There is growing evidence to suggest that patient obesity may increase nursing workload and time taken for clinical care. Design: Integrative review.Methods: A compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
(153 reference statements)
0
12
0
Order By: Relevance
“…Another relevant study reported that negative moods such as anger and boredom affected the emotional eating behaviors of the participants (25). One of the target groups of nurses who provide care and counseling to the public while in direct contact with the public is overweight and obese people (26). Overweight or obese people often have eating disorders (27).…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant study reported that negative moods such as anger and boredom affected the emotional eating behaviors of the participants (25). One of the target groups of nurses who provide care and counseling to the public while in direct contact with the public is overweight and obese people (26). Overweight or obese people often have eating disorders (27).…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare workers must be very skilled when caring for PWO to be able to perform tasks such as measuring blood pressure, performing venipuncture, and examining them (11). Sometimes the quality of PWO care is low due to healthcare workers' inability (29), insufficient skills or training, the lack of healthcare workers, the lack of the necessary equipment (30), the need to spend a lot of time, and the increased burden of care (11). Therefore, other healthcare workers with enough skills and capabilities help.…”
Section: Help-seeking In Performing Clinical Proceduresmentioning
confidence: 99%
“…The increasing admission of PWO and the failure to meet their routine care needs may disturb their safety and comfort (36). Managers should increase the number of human resources, provide and prepare care equipment suitable for these patients in hospitals (11,33), and increase healthcare workers' clinical skills (11). They must encourage a teamwork approach (8) for better and higher-quality care.…”
Section: Help-seeking For Patient Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…We located a second scoping review that found that safe and effective care of patients with Class 3 obesity substantially increases nursing and challenging nurses' safety if training or staffing needs are not met. 42…”
Section: Comprehensive Care For the Patient With Class 3 Obesitymentioning
confidence: 99%